Use of an automaton model to suggest methods for cessation of intractable fibrillatory activity. (1st November 2018) - Ciaccio, Edward J.; Peters, Nicholas S.; Garan, Hasan
Abstract: Background: Atrial fibrillation (AF) is the most common heart arrhythmia, and permanent AF is an intractable medical problem. If cessation of permanent AF were possible, via extensive substrate ablation or multisite stimulation, it could significantly improve the public health. Method: A cellular automaton composed of 576 × 576 computerized grid nodes, described in detail previously, was used to test hypotheses concerning the cessation of fibrillatory electrical activity. A refractory period gradient across the grid, and addition of randomly located nonconducting fibers, were utilized as conditions leading to fibrillatory activity. A premature S1-S2 stimulus was applied to one grid corner, resulting in unidirectional conduction block at some locations, followed by rotational activity and random propagation of activation wavelets throughout the grid, none of which terminated spontaneously. Simulated ablation lesions of dimension 20 × 20 grid nodes, imparted at core locations of rotational activity, and multisite electrode stimulation (MES) applied at nodes where recovery of excitability had occurred, were used in attempts to terminate fibrillatory activity. Six impositions of random fiber location were utilized in separate trials. Results: Simulated ablation lesions eliminated the targeted swirling vortices; however, additional vortices then often appeared at other locations. After ablating approximately one third of the grid area, localized vortices were eliminated, but individual wavelets continued to propagate about longer viable pathways forming at ablation lesions. Thus extensive ablation was unsuccessful in terminating arrhythmia. However, MES applied uniformly throughout the grid, with a coupling interval slightly longer than the maximum refractory period, terminated fibrillatory activity in some trials. More efficaciously, application of MES with a coupling interval half the maximum refractory period of the grid succeeded in capture of activation at all nodes, and when followed by a doubling of the MES coupling interval, resulted in cessation of all fibrillatory activity. Conclusions: It is possible to terminate simulated fibrillatory activity in a computerized grid that would otherwise be intractable, using multisite stimulation with a coupling interval related to the maximum refractory period of the substrate. If each MES stimulating electrode could be individually controlled, it would be possible to apply a stimulation pattern mimicking the normal heart activation sequence. Highlights: Permanent atrial fibrillation (AF) is intractable. An automaton model was used to simulate fibrillatory activity. Simulated ablation changed fibrillatory activity to flutter. Multisite stimulation eliminated fibrillatory activity. Permanent AF may be treatable with multisite stimulation.